2015
DOI: 10.5714/cl.2015.16.1.062
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and thermal properties of polyethylene-based carbonized fibers

Abstract: In this study, carbonized fibers were prepared by using acidically cross-linked LDPE fibers. The surface morphologies of the carbonized fibers were observed by SEM. The effects of cross-linking process temperatures were studied using thermal analyses such as DSC and TGA. The melting and heating enthalpy of the fibers decreased as the cross-linking temperature increased. The cross-linked fibers had a carbonization yield of over 50%. From SEM results the highest yield of carbonized LDPE-based fibers was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…This shows that the oxygen functional groups and surface free energy values can determine the resulting adhesion strengths of the carbon fiber/polarized polypropylene matrix in this system. Practically, the well-known ring-opening crosslinking reaction between amino-silane coupling agents (APS) and polypropylene-co-maleic anhydride can dramatically enhance the mechanical interfacial strength [29][30][31][32][33][34] of a composite. However, we used partially polarized polypropylene (Ma 0.2 -PP 99.8 ) as a matrix.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…This shows that the oxygen functional groups and surface free energy values can determine the resulting adhesion strengths of the carbon fiber/polarized polypropylene matrix in this system. Practically, the well-known ring-opening crosslinking reaction between amino-silane coupling agents (APS) and polypropylene-co-maleic anhydride can dramatically enhance the mechanical interfacial strength [29][30][31][32][33][34] of a composite. However, we used partially polarized polypropylene (Ma 0.2 -PP 99.8 ) as a matrix.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…However, materials used for preparation of higher quality activated carbon cost greater [12]. Searching for low cost activated carbon resources is of great importance in the removal of heavy metals from wastewater [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [48] have shown that LDPE could be used as a precursor and cross-linked by sulfuric acid to obtain a http://carbonlett.org linking density. The sulfonic acid cross-linked method resulted in XLPE with a high cross-linking density, but it lacked cross-linking uniformity and produced surface destruction.…”
Section: Resultsmentioning
confidence: 99%
“…Also, PE has a high carbonization ratio in the carbonization process, and it can be melt spun. Because of these advantages, PE is promising for the manufacture of a low-cost CF [41,48].…”
Section: Radiationmentioning
confidence: 99%